Collaborative Irrationality, Akrasia, and Groupthink: Social Disruptions of Emotion Regulation - Szanto, Thomas (Frontiers in Psychology, 2017)
The present paper proposes an integrative account of social forms of practical irrationality and corresponding disruptions of individual and group-level emotion regulation. I will especially focus on disruptions in emotion regulation by means of collaborative agential and doxastic akrasia. I begin by distinguishing mutual, communal and collaborative forms of akrasia. Such a taxonomy seems all the more needed as, rather surprisingly, in the face of huge philosophical interest in analysing the possibility, structure and mechanisms of individual practical irrationality, with very little exception, there are no comparable accounts of social and collaborative cases. However, I believe that, if it is true that individual akrasia is, in the long run, harmful for those who entertain it, this is even more so in social contexts. I will illustrate this point by drawing on various small group settings, and explore a number of socio-psychological mechanisms underlying collaborative irrationality, in particular groupthink. Specifically, I suggest that in collaborative cases there is what I call a spiralling of practical irrationality at play. I will argue that this is typically correlated and indeed partly due to biases in individual members’ affect control and eventually the group’s with whom the members identify.